BELAJAR MENULIS DENGAN BERCERITA DAN GAMBAR: PENGALAMAN SISWA TUNAGRAHITA DALAM MENYUSUN KALIMAT MELALUI DISKUSI DAN GAMBAR BERSERI - Siti Zulaihah; Jeffry Handhika; Muh. Waskito Ardhi (An Nafi': Multidisciplinary Science, 2026)
Writing simple sentences is a fundamental skill that supports the independence of students with intellectual disabilities. This study aims to explore the learning experiences of students with intellectual disabilities in composing sentences through the combination of the Think Pair Share method and picture series media. This qualitative research uses a phenomenological approach to understand students' personal experiences in learning. The research was conducted at SMPLB Negeri Karangrejo, Madiun Regency, involving students with mild to moderate intellectual disabilities. Data were collected through participatory observation, simple guided interviews, and analysis of students' work. Data were analyzed thematically to identify patterns in learning experiences. The findings show that picture series help students visualize ideas and determine the sequence of stories, while discussions with friends provide opportunities to practice arranging words into sentences verbally before writing. Students feel more confident and motivated when learning involves interactive and visual activities. This study concludes that a combination of cooperative methods and visual media creates a meaningful learning experience for students with intellectual disabilities in developing writing skills.